“Vinha caminhando a pé, para ver se encontrava uma cigana de fé”: o culto aos espíritos ciganos no Catimbó/Jurema do Ylê Axé Nagô Ôxáguã (Caicó/RN) - Vale, Lucas Medeiros de Araújo (2018)
Present in the west since the mid-fifteenth century, those who are now ethnically recognized or recognized as "gypsies" occupy in the imaginary of the other, "non-gypsy", diverse and sometimes dichotomous images. If, on the one hand, they are seen as dirty, smelly, thieves, vagabonds, and cheaters - on the other hand, they are metaphysical beings, holders of magical knowledge and divine gifts, able to access through the cartomancy, or The palm of the hand, facets of the past, present and future. They could also heal, curse, bewitch and act upon the life of anyone, whether they - the gypsies - living or dead, working miracles in their graves, or making themselves present as spirits, in Kardecist centers, Spiritualist gypsy tents, temples Of the “Vale do Amanhecer”, in centers of “Umbanda” and even of the “Jurema Sagrada/Catimbó”. In this dissertation, we seek to reflect on the operations of social and imaginary constructions of know ledge about the gypsy ethnicity in the worship of the Gypsie of the Jurema Sagrada/Catimbó in a "terreiro" that also denominates like of “Candomblé”, taking into account the markers of difference "race" and "religion", and the symbolic and material relationship between the spirits/entities, who are worshiped in this space, and "juremeiros(as)" mediums of double religious belonging. Taking for our analysis the records of our field diary, "pontos cantados" - or "toadas" -, and the interview transcripts collected from the Ylê Axé Nagô Ôxáguiã in Caicó / RN. With this, we aim to understand how religious perform their rituals, (re)signify cultures and appropriate them in their sacred practices.